Antibiotic Resistance Conferred by a Conjugative Plasmid and a Class I Integron in Vibrio cholerae O1 El Tor Strains Isolated in Albania and Italy - Falbo, Vincenzo (American Society for Microbiology, 1999)
Multidrug-resistant Vibrio cholerae O1 El Tor strains isolated during the 1994 outbreak of cholera in Albania and Italy were characterized for the molecular basis of antibiotic resistance. All strains were found to be resistant to tetracycline, streptomycin, spectinomycin, trimethoprim, sulfathiazole, and the vibriostatic compound O/129 (2,4-diamino-6,7-diisopropylteridine). Resistance genes were self-transferable by a conjugative plasmid of about 60 MDa, with the exception of spectinomycin resistance, which was conferred by the aadA1 gene cassette located in the bacterial chromosome within a class 1 integron. The resistance to trimethoprim and O/129 was conferred by the dfrA1 gene, which was present on the plasmid. Although the dfrA1 gene is known to be borne on an integron cassette, class 1, 2, or 3 intI genes were not detected as part of the plasmid DNA from the strains studied.